2014
DOI: 10.3198/jpr2014.01.0003crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of the Novel Wheat Lines L658, L693, L696, and L699, with Resistance to Fusarium Head Blight, Stripe Rust, and Powdery Mildew

Abstract: Four red spring wheat (Triticum aestivum L.) lines, L658 (Reg. No. GP-971, PI 672537), L693 (Reg. No. GP-972, PI 672538), L696 (Reg. No. GP-973, PI 672539), and L699 (Reg. No. GP-974, PI 672540), were developed at the Provincial Key Laboratory of Plant Breeding and Genetics, Sichuan Agricultural University of China from the cross 'MY11'/YU25, the latter of which was derived from a cross between common wheat (Triticum aestivum, 2n = 6x = 42, AABBDD) and Thinopyrum intermedium (Host) Barkworth & D.R. Dewey (2n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
(24 reference statements)
0
23
0
Order By: Relevance
“…No. GP-972, PI 672538) is from F 6:7 families of a cross between MY11 and YU25, the latter being a derivative of a wide cross involving Thinopyrum intermedium [ 17 ]. Genetic analysis demonstrated that stripe rust resistance observed in L693 is conferred by a single dominant gene, YrL693 , which was mapped to chromosome 1B by linkage analysis with simple sequence repeat (SSR) markers and Chinese Spring nulli-tetrasomic lines [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…No. GP-972, PI 672538) is from F 6:7 families of a cross between MY11 and YU25, the latter being a derivative of a wide cross involving Thinopyrum intermedium [ 17 ]. Genetic analysis demonstrated that stripe rust resistance observed in L693 is conferred by a single dominant gene, YrL693 , which was mapped to chromosome 1B by linkage analysis with simple sequence repeat (SSR) markers and Chinese Spring nulli-tetrasomic lines [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the use of Sumai3 in breeding is still unsuccessful (Chen et al 2012), breeders appreciate other germplasm of resistance with some improved and important traits. Previous studies showed that L699 had a strong FHB resistance, which was similar to those of Sumai3 and Wangshuibai (Zhang et al 2011;Liu et al 2015;Yang et al 2016). However, it does not meet the requirement for FHB resistance.…”
Section: Discussionmentioning
confidence: 68%
“…In China, FHB epidemics have frequently occurred in the middle to lower valleys of the Yangtze River (Yao & Lu 2000). In recent years, FHB has spread to the southwest of China, including Sichuan Province (Zhang et al 2011;Liu et al 2015;Yang et al 2016), where the climate was warm and rainy. Furthermore, FHB is also a fungal disease threatening food and economic security due to its contamination with mycotoxins, decreasing the wheat yield and quality (Zwart et al 2008).…”
Section: Abstract: Agronomic Trait; Fhb; Resistance Evaluation; Tritimentioning
confidence: 99%
“…From agronomical traits and application standpoints of view, we developed the following four spring wheat lines: L658 (PI 672537), L693 (PI 672538), L696 (PI 672539), and L699 (PI 672540). These lines exhibited excellent agronomic traits, including yield and resistance to Fusarium head blight conferred by FhbL693a and FhbL693b [ 24 ], to stripe rust conferred by YrL693 [ 25 ] and to powdery mildew conferred by Pm40 [ 22 , 23 , 26 , 27 ]. Though the pedigree of PI 672538 includes Th .…”
Section: Introductionmentioning
confidence: 99%
“…Pm21 still exhibits strong resistance to powdery mildew and is the most commonly employed powdery mildew resistance gene in Chinese breeding programs [ 19 ], but new isolates that are highly virulent to Pm21 have been reported [ 29 , 30 ]. However, Pm40 confers strong resistance to powdery mildew in the field of both Henna and Sichuan Provinces of China [ 21 , 25 26 ]), and this gene is effective against nearly all isolates collected from the main wheat growing regions of China [ 23 ]. Thus, Pm40 may be widely used in future Chinese breeding programs as an alternative to Pm21 , necessitating the identification and prioritization of molecular markers closely associated with Pm40 by marker-assisted selection is an important task.…”
Section: Introductionmentioning
confidence: 99%